Handling Perishable Food Stuff for Quality Assurance and its Effect on Quality and Price a Study of Yanlemo Market, Kumbotso L.G.A of Kano State - Lawan, Hadiza (Richtmann Publishing, 2012)
The purpose of this research work is to find out how perishable food stuffs are handled in Yanlemo marketand its effect on quality and price of commodity. Questionnaires were administered to 50 randomlysampled traders about handling of perishable stuff during transportation, cleanliness, display, storage, howit affects quality and price and the problems associated with the its handling. The study revealed that thereis little or no knowledge on proper handling since 75% of the respondents are within the range of nonformal to O’level of education. More than 75% displayed their items outside shops which attract dust, air,sunlight, flies and other climatic conditions. While they realized that quality of their item is the main factorthat stimulate customers and that poor handling depreciate the value of the item, 40% of the respondentssuggested that for effective quality assurance in the business of perishable items cooperative efforts of 40%and Government role of 30% should be involved.